EDUCATIONAL AND TECHNICAL CONDITIONS FOR TEACHING WRITING - Shavazova Nilufar Musayevna (Western European Studies, 2024)
Teaching writing is a complex process, it is considered a psycholinguistic process that depends on the character of the student, on the genetic possibility. Children who have just arrived at school are incredibly difficult to teach writing. Also, teaching children to write is conducted directly in connection with the process of reading. There are several conditions for teaching writing, under which a beautiful writing qualification is formed in students. This article will talk about these conditions
Keywords: graphic skills; orthographic skills; technical conditions; educational conditions